Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Asuransi Jiwa (Studi Kasus PT. Maandiri Inhealth Cabang Sibolga) - Imsar, Imsar; Tambunan, Khairina; Manullang, Adinda Syariana Dewi (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Adinda sya'riana Dewi Manullang 2022 " analysis of factors affecting the demand for Life Insurance (iHealth Sibolga Branch Independent case Study)â€ with Imsar supervisor I. M.Si and supervisor II Khairina Tambunan may.This study aims to analyze the factors that affect the demand for life insurance at PT Mandiri Inhealth.This research data obtained from questionnaires (primary) and some observations and direct interviews with parties related to life insurance include the identity of respondents, and matters relating to the policy (contents of the agreement) customers who use Life Insurance Services at PT Mandiri Inhealth, family income, insurance costs or premiums, number of children, age of the respondent.The results showed that the variable income (X1) and variable income (X1) have a positive and significant effect on the demand for life insurance at PT Mandiri Inhealth. While the variable number of children (X2) has a negative and insignificant effect on the demand for life insurance at PT Mandiri Inhealth, the variable age (X3) has a positive and significant effect on the demand for life insurance at PT Mandiri Inhealth.